In Search of Philippine Chaebols - Mendoza, Ronald U (Archīum Ateneo, 2019)
Historically, large-scale capital-intensive industries have played a key role in many developing countries' industrialization. Some countries created state-owned enterprises (SOEs) with heavy government intervention and support to complete production chains to meet demand and export markets. South Korea, for one, has been known for the success of the chaebol, a large family-controlled and diversified private company that received strong government industrial policy support. Similar to South Korean chaebols, the Philippines have conglomerates, large, family-owned corporations comprised of smaller subsidiaries with a considerable footprint on the national economy. This paper fills a gap in the policy literature through the review of historical developments in selected Philippine industries and where key players tend to dominate. Furthermore, this paper shows evidence that some Philippine conglomerates displayed expansion behavior similar to East Asian economies like South Korea. The study also uncovers behavioral trends of these firms' diversification into non-traded service industries that were less conducive to rapid industrial development. Finally, it concludes with a brief discussion on how Philippine conglomerates contribute to the country's inclusive development agenda.